Identifying predictors of high quality care in English general practice: observational study. Issue 7316 (6th October 2001) - Campbell, S M; Hann, M; Hacker, J; Burns, C; Oliver, D; Thapar, A; Mead, N; Safran, D Gelb; Roland, M O
Abstract: Objectives: To assess variation in the quality of care in general practice and identify factors associated with high quality care. Design: Observational study. Setting: Stratified random sample of 60 general practices in six areas of England. Outcome measures: Quality of management of chronic disease (angina, asthma in adults, and type 2 diabetes) and preventive care (rates of uptake for immunisation and cervical smear), access to care, continuity of care, and interpersonal care (general practice assessment survey). Multiple logistic regression with multilevel modelling was used to relate each of the outcome variables to practice size, routine booking interval for consultations, socioeconomic deprivation, and team climate. Results: Quality of clinical care varied substantially, and access to care, continuity of care, and interpersonal care varied moderately. Scores for asthma, diabetes, and angina were 67%, 21%, and 17% higher in practices with 10 minute booking intervals for consultations compared with practices with five minute booking intervals. Diabetes care was better in larger practices and in practices where staff reported better team climate. Access to care was better in small practices. Preventive care was worse in practices located in socioeconomically deprived areas. Scores for satisfaction, continuity of care, and access to care were higher in practices where staff reported better team climate. Conclusions: Longer consultation times are essential for providing high quality clinical care. Good teamworking is a key part of providing high quality care across a range of areas and may need specific support if quality of care is to be improved. Additional support is needed to provide preventive care to deprived populations. No single type of practice has a monopoly on high quality care: different types of practice may have different strengths.